2019
DOI: 10.3390/ijms21010185
|View full text |Cite
|
Sign up to set email alerts
|

Integration of ATAC-Seq and RNA-Seq Identifies Key Genes in Light-Induced Primordia Formation of Sparassis latifolia

Abstract: Light is an essential environmental factor for Sparassis latifolia primordia formation, but the molecular mechanism is still unclear. In this study, differential expression profiling of light-induced primordia formation (LIPF) was established by integrating the assay for transposase accessible chromatin by sequencing (ATAC-seq) and RNA-seq technology. The integrated results from the ATAC-seq and RNA-seq showed 13 down-regulated genes and 17 up-regulated genes in both the L vs. D and P vs. D groups, for both me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…We established that 24% of DARs are associated with upDEGs or downDEGs, suggesting that a significant proportion of regions that gain or lose chromatin accessibility experience changes in transcription rates. Although not many studies have been published in plants directly comparing changes in chromatin accessibility with changes in gene expression, ATAC-seq and RNA-seq assays in the parasitic fungus Sparassis latifolia showed that 23% of DARs were associated with upDEGs or downDEGs between control cells and light-induced cells ( 42 ). In addition to this first set of DARs, we identified 1,748 DEGs not associated with detectable changes in chromatin accessibility and another 5,509 DARs for which the closest genes did not show differential gene expression, suggesting that changes in gene expression do not necessarily require a change in chromatin accessibility and that changes in chromatin accessibility do not necessarily affect the expression of the closest transcriptional unit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We established that 24% of DARs are associated with upDEGs or downDEGs, suggesting that a significant proportion of regions that gain or lose chromatin accessibility experience changes in transcription rates. Although not many studies have been published in plants directly comparing changes in chromatin accessibility with changes in gene expression, ATAC-seq and RNA-seq assays in the parasitic fungus Sparassis latifolia showed that 23% of DARs were associated with upDEGs or downDEGs between control cells and light-induced cells ( 42 ). In addition to this first set of DARs, we identified 1,748 DEGs not associated with detectable changes in chromatin accessibility and another 5,509 DARs for which the closest genes did not show differential gene expression, suggesting that changes in gene expression do not necessarily require a change in chromatin accessibility and that changes in chromatin accessibility do not necessarily affect the expression of the closest transcriptional unit.…”
Section: Discussionmentioning
confidence: 99%
“…One such technique has gained widespread use due to its simplicity and low requirement for input of biological material: assay for transposase-accessible chromatin, followed by sequencing (ATAC-seq) ( 33 , 34 ). This method has since been employed to characterize and compare the dynamics of chromatin accessibility between cell types and different growth conditions ( 35 – 42 ). In this study, we applied ATAC-seq, together with transcriptome deep sequencing (RNA-seq) to the roots of Arabidopsis wild-type (WT) and phr1 phl2 seedlings to explore the relationship between chromatin accessibility and differential gene expression during Pi limitation, as well as the potential role of the transcriptional regulators PHR1 and PHL2.…”
mentioning
confidence: 99%
“…The integration of ATAC-seq and RNA-seq enables the reveal of TF-targeted genes and their transcripts [187,188]. Chromatin conformation capture analysis (3C) technology and its several derivatives including circular chromosome conformation capture (4C), carbon copy chromosome conformation capture (5C), ChIP-Loop, Hi-C and capture Hi-C were developed and improved to detect chromatin structure as well as unknown interacting regions [189][190][191].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, our group reported that the S. latifolia has a size of 48.13 megabases (Mb) and 12,471 predicted genes (Xiao et al, 2018). Based on this genome sequence, we explored the mechanism of light response and primordia formation of S. latifolia (Xiao et al, 2017;Yang et al, 2019). The genome of S. latifolia was also deposited at the Joint Genome Institute (JGI, project Id: 1105659) and Genebank (PRJNA562364), consiting of 35.66 Mb and 39.32 Mb genome lengths, respectivily.…”
Section: Introductionmentioning
confidence: 99%